Symptom Factors and Neuropsychological Performance in Collegiate Athletes with Chronic Concussion Symptoms. (2nd November 2020) - Guty, Erin; Riegler, Kaitlin; Meyer, Jessica; Walter, Alexa E; Slobounov, Semyon M; Arnett, Peter
Abstract: Objective: The present study explored the relationship between specific types of postconcussion symptoms and cognitive outcomes in student–athletes with chronic concussion symptoms. Method: Forty student–athletes with chronic concussion symptoms were given a battery of neuropsychological tests and rated themselves on a variety of postconcussion symptoms, which included the following factors derived from prior work: Physical, Sleep, Cognitive, Affective, and Headache. Cognitive outcomes included performance on composites for the memory and attention/executive functioning speed tests, respectively. The following covariates were also explored: Sex, depression symptoms, number of previous concussions, and time since injury. Results: Headache was the only individual symptom factor that significantly ( p < .05) predicted worse attention/executive functioning performance. None of the symptom factors were significantly related to memory performance over and above the variable of time since injury, such that longer time since injury was related to worse memory performance. Conclusion: Comparable to work examining symptom predictors of cognitive outcomes in acutely concussed samples, headache predicted worse attention/executive functioning performance. Additionally, we found that the longer athletes had been symptomatic since injury, the "worse" their memory functioning. Understanding how headache and the length of time an individual is symptomatic are related to cognitive outcomes can help inform treatment and recommendations for athletes with prolonged symptom recovery.